(untitled) (Medicine Anthropology Theory, 2019)
This think piece asks readers to consider how the science of anthropology has contributed to (re)categorization and imaginaries of gender, class, and the state in the context of public and global health interventions. Anthropological work on HIV has since its inception questioned the public health categories of those considered at highest risk for HIV, while simultaneously helping to reconstitute those categories, as well as definitions of risk, especially in relation to the concept of vulnerability. While anthropological research on HIV is replete with critiques of categorization as a mode of governance, most often in reference to global health and development apparatuses, anthropologists rarely reflect on the role the discipline might play in co-creating those categories to ‘make up people’ and reproduce geopolitical norms. The propositions I lay out in this think piece stem from my experience researching the emergence of public and global health categories in various national settings in eastern and southern Africa win the context of HIV interventions.